Historia ambiental y ecocrítica para arquitectos. El potencial de las humanidades ambientales para la arquitectura y el urbanismo - Santini, Tyana (Universidad ORT Uruguay, 2017)
The environmental humanities have emerged from traditional academic disciplines with a long tradition in the study of the man-nature relationship, and share today the purpose of encouraging a more careful consideration of our assumptions regarding the environment and its problems. After a brief discussion of the conflicting views of environmental issues in higher education, this article explores the potential intersections between environmental humanities and architecture in three areas: material, theoretical,and management. The inclusion of environmental perspectives from other fields can offer information on specific changes of a natural or urban landscape, analysis of imagined or symbolic natures, or critical views on the effects on our ideas of nature on environmental management. Through this discussion, this article hopes to contribute to the integration of new perspectives on nature into the study of the relationship between the built environment and nature.